Statistical Analysis of Cutting Force and Vibration in Turning X5CrNi18-10 Steel - Csaba Felhő; Tanuj Namboodri (Applied Sciences)
X5CrNi18-10 is a corrosion-resistant steel that has become popular in the automotive, marine, food, nuclear, and other industries. Chromium alloyed in the X5CrNi18-10 increases the material’s toughness, which influences the cutting phenomena such as the cutting force and vibration. It is necessary to investigate the effect of the machining parameters on the X5CrNi18-10 turning, particularly the feed, which has significant effects on the cutting phenomena. The objective of this research is to investigate the correlation between the feed and cutting phenomena to improve the product quality, reduce machining disruptions, and optimize the parameters for a low cutting speed and vibration. Statistical analysis has shown promise in identifying the impact of variables using correlation analysis and estimated marginal means plots. This study highlights the findings of the Pearson’s correlation analysis between the feed, active cutting force, and active vibration as well as the estimated marginal means plots between the machining parameters and cutting phenomena. The results indicate that there is a strong correlation between the feed and active cutting force with a coefficient of correlation of 0.688, as well as the feed and active vibration with a coefficient of correlation of 0.697. The estimated marginal means plots indicate that as the cutting speed increases, the value of the active vibration and the active force decreases.